A Political Scientist and Voting-Rights Litigation: The Case of the 1966 Texas Registration Statute - Walter Dean Burnham (Washington University Law Quarterly, 1971)
It is not the purpose of this Article to deal at length with the evolution of judicial doctrine and legislative action affecting voting rights. Rather, I shall attempt a sketch of two things here: the background and implications of a recently decided case in which a state’s personal-registration statute was struck down by a federal court, and my own involvement in the case.